The prevalence of syphilis infection and its associated factors among psychiatric patients at Mankweng Hospital, Limpopo Province - Lebotsa, Matholwane Salminah (My University, 2024)
Syphilis is a sexually transmitted infection that is prevalent among the sexually active age group of 15 to 49 years. In psychiatry, neurosyphilis may cause or aggravate mental illness, however data relating to the infection prevalence is scarce in this population. As a result, the current study was aimed at determining the prevalence of and factors associated with syphilis infection in psychiatric patients. A quantitative cross-sectional descriptive study was conducted where data was collected from clinical files, using data collection forms. The non-treponemal RPR, CSF-VDRL and treponemal TPHA tests were used to make the diagnosis of syphilis infection. Four hundred (400) case files were reviewed and descriptive statistics were used to analyse the data where a p-value of <0.05 was considered statistically significant. An overall syphilis infection prevalence of 1.8% was found. Syphilis was more prevalent in females than males. Significant factors associated with syphilis infection included age, marital status, level of education and negative HIV status. Findings from the study support the routine screening of syphilis infection among psychiatry patients and emphasize the need to intensify prevention strategies in this population.
Thesis (M. Med. (Psychiatry)) -- University of Limpopo, 2024
Keywords: Syphilis infection; Prevalence; Associated factors; Syphilis; Syphilis -- Complications; Neurosyphilis